2013
DOI: 10.1183/09031936.00110913
|View full text |Cite
|
Sign up to set email alerts
|

Detection and severity grading of COPD exacerbations using the exacerbations of chronic pulmonary disease tool (EXACT)

Abstract: Uncertainty exists over the ability of the exacerbations of chronic pulmonary disease tool (EXACT) patient-reported outcome diary to quantify exacerbation severity and frequency. To clarify this, we investigated the ability of the EXACT to assess severity of exacerbations and examined the relationship between exacerbations diagnosed using London chronic obstructive pulmonary disease (COPD) cohort diary cards, physician review and symptom-defined events using the EXACT.58 patients enrolled in the London Chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 26 publications
0
67
0
Order By: Relevance
“…For this reason, some instruments such as the Exacerbations of Chronic Pulmonary Disease Tool or COPD Assessment Test (CAT) may be useful in reporting and assessing the severity of exacerbations [27,28]. To date, no sputum or plasma biomarker with good sensitivity and specificity has been found that can identify either the presence or severity of an exacerbation.…”
Section: Defining Copd Exacerbationsmentioning
confidence: 99%
“…For this reason, some instruments such as the Exacerbations of Chronic Pulmonary Disease Tool or COPD Assessment Test (CAT) may be useful in reporting and assessing the severity of exacerbations [27,28]. To date, no sputum or plasma biomarker with good sensitivity and specificity has been found that can identify either the presence or severity of an exacerbation.…”
Section: Defining Copd Exacerbationsmentioning
confidence: 99%
“…A lot of time and money was spent on development of EXACT. Before we throw out the baby with the bathwater based on the results of the study by MACKAY et al [10], it is worth noting potential limitations of this study which may have affected results.…”
mentioning
confidence: 99%
“…One such new measurement tool is the Exacerbations of Chronic Pulmonary Disease Tool (EXACT), a 14-item, patient-reported daily symptom diary that attempts to accurately capture the frequency, severity, and duration of exacerbations, and which is meant to be used in clinical trials and cohort studies of COPD patients [8]. A tool such as EXACT is desperately needed by COPD clinical researchers [9], assuming that it works.In this issue of the European Respiratory Journal, MACKAY et al [10] have attempted to test EXACT to see if it fulfils its expected functions. The investigators prospectively administered EXACT as well as their previously validated London COPD Cohort diary cards to 58 patients in their COPD cohort on a daily basis [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations